Translational Animal Models to Study Endometriosis-Associated Infertility - Grümmer, Ruth (Seminars in Reproductive Medicine, 2013)
Although there is an apparent association between endometriosis and impaired fertility, the pathophysiology of the reduced fecundity in women with endometriosis still remains unclear. Reproduction is a complex and multifactorial process, and possible factors contributing to the reduced fertility of endometriosis patients include defective function of the ovary, gametes, and endometrium as well as developmental disorders of the embryo. Because controlled experiments in humans are limited due to ethical reasons, experimental animal models have been developed mainly in nonhuman primates and laboratory rodents by induction of endometriosis via autologous transplantation of endometrial tissue. Animals with induced endometriosis reveal an impairment of fecundity similar to the situation described for humans and have been used to identify effects of ectopic endometrial tissue on adhesion formation, peritoneal fluid composition, ovarian function, endometrial gene expression, and embryo implantation. These animal models of endometriosis yield a valuable tool to study the mechanisms of endometriosis-associated infertility especially during the onset of the disease that cannot be investigated in women.
Keywords: endometriosis; infertility; animal model; receptivity